Rancang Bangun Alat Uji Jominy (Jominy Hardenability Test) - Herdi Susanto; Joli Supardi; T Sayuthi; Hendra Marliadi (universitas teuku umar, 2018)
Research purposes to add practical tool for students in the Department of Mechanical Engineering , University of Teuku Umar . especially for the practice of subjects Physical Metallurgy , engineering design is done with the steps: a literature study , design , manufacture and testing based on ASTM A 255-02 . Results frame design with dimensions of 175x100x100 cm , 56cmx6cmx5 mm specimen holder with a hole diameter of 26.5 mm , water tank diameter of 56 cm and a height of 45 cm , an electric pump with a rotation of 2850 rpm . Testing test equipment using specimens ASTM A 255-02 . Frame assembly using steel L profiles 40 X40 mm and 5 mm strip plate , water tanks with a capacity of 100 liters , the installation of water pipes using the 1½ inch PVC . the results of tests performed on the low-carbon steel material , equipment can function and work properly Keywords : design, assembly, jominy hardenability test , ASTM A255-02